Teachers and specialist figures in network in the read-write learning disabilities - Mirca Montanari; Giorgia Ruzzante (Firenze University Press, 2017)
The contribution intends to propose a pedagogical reflection on the issue of read-write difficulties, starting with the greater awareness present on the subject today, in the perspective of the inclusive approach and networking work that sees school partnership of the family and territory's services.   Docenti e figure specialistiche in rete nelle difficoltà di letto-scrittura Il contributo intende proporre una riflessione pedagogica sul tema delle difficoltà di letto-scrittura, a partire dalla maggiore consapevolezza presente oggi sul tema, nella prospettiva di approccio didattico inclusivo e del lavoro di rete che vede la scuola partner della famiglia e dei servizi nel territorio.